Thin Heterojunctions and Spatially Separated Cocatalysts To Simultaneously Reduce Bulk and Surface Recombination in Photocatalysts. (22nd July 2016) - Li, Ang; Chang, Xiaoxia; Huang, Zhiqi; Li, Chengcheng; Wei, Yijia; Zhang, Lei; Wang, Tuo; Gong, Jinlong
Abstract: Efficient charge separation and light absorption are crucial for solar energy conversion over solid photocatalysts. This paper describes the construction of Pt@TiO2 @In2 O3 @MnO x mesoporous hollow spheres (PTIM‐MSs) for highly efficient photocatalytic oxidation. TiO2 –In2 O3 double‐layered shells were selectively decorated with Pt nanoparticles and MnO x on the inner and outer surfaces, respectively. The spatially separated cocatalysts drive electrons and holes near the surface to flow in opposite directions, while the thin heterogeneous shell separates the charges generated in the bulk phase. The synergy between the thin heterojunctions and the spatially separated cocatalysts can simultaneously reduce bulk and surface/subsurface recombination. In2 O3 also serves as a sensitizer to enhance light absorption. The PTIM‐MSs exhibit high photocatalytic activity for both water and alcohol oxidation.